MULTILITERACIES PEDAGOGY: A CASE STUDY OF CRITICAL READING IN ELT CLASSROOM BY IMPLEMENTING SITUATED PRACTICE - Mikhael Misa (English Review: Journal of English Education, 2023)
This research study aims to investigate the implementation of situated practice in multiliteracy teaching within an English Language Teaching (ELT) classroom, specifically focusing on critical reading activities. This study employed a qualitative approach. The study focuses on lecturers delivering lectures to third-year students enrolled in the English Study Program at Teacher Training and Educational Faculty, Timor University, East Nusa Tenggara Province. To analyze the data gathered and insights linked to the situated practice of multiliterate teaching in the ELT classroom, data were transcribed, encoded, displayed, and interpreted. The collected data is subjected to a comprehensive analysis to assess the effectiveness of implementing the situated practice of the multiliteracies pedagogical framework through students' critical reading. The findings revealed a significant enhancement in students' critical thinking abilities due to engaging in a series of learning activities within the Multiliteracy Pedagogy framework.